Walter Van Beirendonck : dream the world awake. - Bogaert, Christelle; Van den Bossche, Hadewych (Tielt : Lannoo, 2011)
Fonds Suzan Daniel (FSD)
Tentoonstellingscatalogus, MOMU Modemuseum Antwerpen 14 september 2011 - 19 februari 2012
Nederlands
Monografie